Prospective Analysis on the Topic of Similarity: Designing a Hypothetical Learning Trajectory to Overcome Learning Obstacles (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
This research is part of Didactical Design Research (DDR) aimed at developing a Hypothetical Learning Trajectory (HLT) in the concept of similarity learning. This study focuses on the prospective analysis stage within DDR. The HLT developed in this research is the result of identifying potential learning obstacles that may arise during the process of similarity learning. Data was collected through five steps in the prospective analysis: 1) cognitive development of seventh-grade students in middle school; 2) research on the topic of similarity and related research findings; 3) curriculum analysis of mathematics textbooks using praxeological theory; 4) reflection and evaluation of learning obstacles; 5) anticipation of student responses and pedagogical strategies. Data collection techniques used were literature study and Praxeology analysis within the Anthropological Theory of Didactics (ATD). The obtained data was then analyzed thematically to identify and understand learning obstacles in the topic of similarity, as well as to design an HLT to address these obstacles. This research revealed difficulties experienced by students in understanding the concept of similarity, such as a lack of initial understanding of scale and magnification concepts, difficulties in comprehending the relationship between ratios and scale factors previously learned, and a lack of relevant task design sequence related to the application of similarity in everyday life. The conclusion of this research is that designing an effective online HLT to overcome learning obstacles in the topic of similarity requires a student-centered approach, the use of active learning strategies, and interactive student engagement. Additionally, it is important to encourage students to think critically and connect concepts to everyday life.